Anthraquinone-2, 6-disulfamidic acid: an anolyte with low decomposition rates at elevated temperatures. Issue 61 (3rd December 2021) - Rohland, Philip; Schreyer, Kristin; Hager, Martin D.; Schubert, Ulrich S.
Abstract : A new anthraquinone based anolyte material for redox flow batteries revealed an extraordinarily high stability at elevated electrolyte temperatures. Abstract : A new sulfamidic acid anthraquinone derivative was synthesized from 2, 6-diaminoanthraquinone with high yields, designed for utilization in redox flow batteries. The active material was investigated with cyclic voltammetry, revealing a reversible redox reaction at approximately −0.65 V vs. Ag/AgCl at pH-values above 12. A stress test in a redox flow battery was applied with hold times at critical states of charge and at 32 °C as well as at 60 °C. Furthermore, the stability was investigated at the maximum concentration of the anolyte. All in all, the material showed the lowest decomposition rates at 60 °C reported so far for an organic anolyte in a redox flow battery.